PENGARUH STANDAR AKUNTANSI PEMERINTAH, SISTEM PELAPORAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA PEMERINTAH DENGAN PENGENDALIAN AKUNTANSI SEBAGAI VARIABEL MODERASI - Fifi Juliastuti Syarif; Memen Suwandi; Nur Rahmah Sari (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to examine the effect of government accounting standards, reporting systems, and clarity of budget targets on government performance accountability with accounting control as a moderating variable. This research is a quantitative research with associative research approach. This research was conducted at the Bulukumba Regency Government. The data collection method in this study used a questionnaire method using a purposive sampling method with a total of 102 respondents. Data analysis used multiple regression analysis and a moderation test using Moderate Regression Analysis (MRA) or interaction test. The results of this study indicate that government accounting standards, reporting systems, and clarity of budget targets have a positive and significant impact on government performance accountability. Accounting control is able to moderate government accounting standards and reporting systems on government performance accountability, while accounting control does not moderate the clarity of budget targets on government performance accountability.